Role of the Membrane-Proximal Domain in the Initial Stages of Human Immunodeficiency Virus Type 1 Envelope Glycoprotein-Mediated Membrane Fusion - Muñoz-Barroso, Isabel (American Society for Microbiology, 1999)
We have examined mutations in the ectodomain of the human immunodeficiency virus type 1 transmembrane glycoprotein gp41 within a region immediately adjacent to the membrane-spanning domain for their effect on the outcome of the fusion cascade. Using the recently developed three-color assay (I. Muñoz-Barroso, S. Durell, K. Sakaguchi, E. Appella, and R. Blumenthal, J. Cell Biol. 140:315–323, 1998), we have assessed the ability of the mutant gp41s to transfer lipid and small solutes from susceptible target cells to the gp120-gp41-expressing cells. The results were compared with the syncytium-inducing capabilities of these gp41 mutants. Two mutant proteins were incapable of mediating both dye transfer and syncytium formation. Two mutant proteins mediated dye transfer but were less effective at inducing syncytium formation than was wild-type gp41. The most interesting mutant proteins were those that were not capable of inducing syncytium formation but still mediated dye transfer, indicating that the fusion cascade was blocked beyond the stage of small fusion pore formation. Fusion mediated by the mutant gp41s was inhibited by the peptides DP178 and C34.